2009
DOI: 10.2967/jnumed.108.058628
|View full text |Cite
|
Sign up to set email alerts
|

HRRT Versus HR+ Human Brain PET Studies: An Interscanner Test–Retest Study

Abstract: The high-resolution research tomograph (HRRT) is a dedicated human brain PET scanner. The purpose of this study was to compare the quantitative accuracy of the HRRT with that of the clinical HR1 PET scanner and to assess effects of differences in spatial resolution between both scanners (;2.7 mm and ;7.0 mm for HRRT and HR1, respectively). Methods: Paired 11 Cflumazenil scans of 7 healthy volunteers were assessed. For each volunteer, dynamic scans (including arterial sampling) were acquired on both scanners on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…In Figure 5, parametric V T images are shown for HR + PVC-NAW-OSEM and HRRT OP-OSEM, together with the ratio of both images. Although no large differences in cortical regions were observed, there were some larger differences in white matter regions ( Figure 5, right image), which is in agreement with a previous study (van Velden et al, 2009a).…”
Section: Phantom Studysupporting
confidence: 93%
See 3 more Smart Citations
“…In Figure 5, parametric V T images are shown for HR + PVC-NAW-OSEM and HRRT OP-OSEM, together with the ratio of both images. Although no large differences in cortical regions were observed, there were some larger differences in white matter regions ( Figure 5, right image), which is in agreement with a previous study (van Velden et al, 2009a).…”
Section: Phantom Studysupporting
confidence: 93%
“…The high test-retest values are, at least in part, a result of differences in scanner performance attributed to, e.g., differences in attenuation (van Velden et al, 2008) and scatter (van Velden et al, 2009a) correction, even though good resolution matching was observed in the phantom study. This difference in performance of attenuation and scatter corrections is therefore seen in all low-resolution HR + versus HRRT comparisons in this study, i.e., most correlation slopes (fixed intercepts) are < 1.0.…”
Section: Test-retest Variabilitymentioning
confidence: 86%
See 2 more Smart Citations
“…We also invited Cho et al [15] from Gachon University in Korea to share with the readers their experience with an affiliated PET-MRI system, that is the side-by-side arrangement of a 7T MRI and a brain-only high-resolution research brain tomograph (HHRT) [16]. While this set-up is unique and not commercially available, it does offer insight into where PET-MRI could go in the future and sets the stage for considering advancing on the technological platform if there are well-defined clinical needs or research requirements.…”
mentioning
confidence: 99%